ASSESSING AND OPTIMIZING THE PERFORMANCE OF A SHELL AND TUBE HEAT EXCHANGER (E-2502) IN PHOSPHORIC ACID PRODUCTION: A CASE STUDY AT PT. PETROKIMIA GRESIK - Saputro, Erwan Adi; Lutfiananda, Delfian; Pratiwi, Annisa Kurnia; Nugroho, Sutra Amelia (International Journal of Mechanical Engineering Technologies and Applications, 2024)
PT. Petrokimia Gresik, established with a construction contract on August 10, 1964, stands as Indonesia's most comprehensive fertilizer factory. The company comprises various departments, including the Production Department IIIA, specializing in Phosphoric Acid Production. The objective of assessing the efficiency of a shell and tube cooler-type heat exchanger is to evaluate its performance, determining compliance with design specifications and identifying the need for cleaning and maintenance. The utilized heat exchanger, of the shell and tube type, employs water as its cooling source. According to design calculations conducted between September 13 and September 18, 2023, the expected efficiency of the cooler-type heat exchanger is 91.44%. However, actual data analysis over six days reveals a significant drop in efficiency, registering below 50%. A comparison between design and actual data suggests a decline in efficiency for the E-2502 cooler type. The decrease is attributed to substantial scaling in the E-2502 Heat Exchanger, stemming from the cooled P2O5 Acid solution and resulting in deposition during the heat transfer process. Consequently, it is imperative to initiate a cleaning process for the cooler-type heat exchanger to optimize the heat transfer mechanism.